2007
DOI: 10.1111/j.1365-313x.2007.03371.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene trap lines identify Arabidopsis genes expressed in stomatal guard cells

Abstract: SummaryWe employed a gene trap approach to identify genes expressed in stomatal guard cells of Arabidopsis thaliana. We examined patterns of reporter gene expression in approximately 20 000 gene trap lines, and recovered five lines with exclusive or preferential expression in stomata. The screen yielded two insertions in annotated genes, encoding the CYTOCHROME P450 86A2 (CYP86A2) mono-oxygenase, and the PLEIOTROPIC DRUG RESISTANCE 3 (AtPDR3) transporter. Expression of the trapped genes in guard cells was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 45 publications
2
78
0
Order By: Relevance
“…The identification of highly specific guard cell promoters (Müller-Röber et al, 1994;Cominelli et al, 2005) and transcription factors (Cominelli et al, 2010;Yoo et al, 2010), the production of guard cell enhancer trap lines (Gardner et al, 2009), and the ability to induce transient expression in guard cells (Rusconi et al, 2013) open up new exciting potential approaches to not only fully understand signaling and transduction pathways in guard cells but also to provide us with the tools to manipulate guard cell metabolism in order to improve plant WUE. Such tools have greatly improved our understanding of the molecular networks that control guard cell perception of and response to internal and external environmental cues and have provided possible candidates for manipulation (Galbiati et al, 2008;Rusconi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of highly specific guard cell promoters (Müller-Röber et al, 1994;Cominelli et al, 2005) and transcription factors (Cominelli et al, 2010;Yoo et al, 2010), the production of guard cell enhancer trap lines (Gardner et al, 2009), and the ability to induce transient expression in guard cells (Rusconi et al, 2013) open up new exciting potential approaches to not only fully understand signaling and transduction pathways in guard cells but also to provide us with the tools to manipulate guard cell metabolism in order to improve plant WUE. Such tools have greatly improved our understanding of the molecular networks that control guard cell perception of and response to internal and external environmental cues and have provided possible candidates for manipulation (Galbiati et al, 2008;Rusconi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This collection was generated by a gene trapping approach based on the Ac/Ds transposon system of maize (Sundaresan et al 1995): the different lines are characterized by the insertion of a modified Ds element (DsG) containing the nptII gene, conferring kanamycin resistance and the GUS reporter gene. In this way a line in which the DsG element is inserted in the correct orientation in the gene of interest, can be informative regarding both the function and the expression pattern of the disrupted gene (Galbiati et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, gene trap lines are useful tools for the identification of organ-, tissue-and cell-specific expression patterns (Galbiati et al 2008), thus to try to obtain a more detailed picture of the CAM2 expression profile we analysed the localization of GUS activity in the cam2-2 line.…”
Section: Expression Analysis Of Cam2 Genementioning
confidence: 99%
“…S4). Galbiati et al 36 suggested that a cluster of at least 3 (T/A)AAAG elements located on the same strand within a 100-bp region is important for guard cell-specific gene expression. Both Col-0 and Ws-2 have several such clusters (Supplemental Fig.…”
Section: The Slac1 Transcript Level In Guard Cells Is Low In Ws-2mentioning
confidence: 99%